2022
DOI: 10.1002/mds.28952
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Subthalamic Nucleus Deep Brain Stimulation to the Improvement in Motor Functions and Quality of Life

Abstract: A BS TRACT:Background: Subthalamic nucleus deep brain stimulation (STN-DBS) effectively treats motor symptoms and quality of life (QoL) of advanced and fluctuating early Parkinson's disease. Little is known about the relation between electrode position and changes in symptom control and ultimately QoL. Objectives: The relation between the stimulated part of the STN and clinical outcomes, including the motor score of the Unified Parkinson's Disease Rating Scale (UPDRS) and the quality-of-life questionnaire, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…The ~ 9% improvement in the PDQ39 summary index reported in our cohort is in line with results reported in a previous short-term neurological day clinic (Fründt et al 2018) as well as the 24-month results of the aforementioned STN-DBS trial (Schuepbach et al 2013). Interestingly, the PDQ39 improvement reported here exceeds those reported following other one-dimensional approaches (Schuepbach et al 2013;Tomlinson et al 2014;Gray et al 2022;Tödt et al 2022).…”
Section: Improvements Of Motor and Non-motor Symptoms As Well As Qolsupporting
confidence: 92%
See 1 more Smart Citation
“…The ~ 9% improvement in the PDQ39 summary index reported in our cohort is in line with results reported in a previous short-term neurological day clinic (Fründt et al 2018) as well as the 24-month results of the aforementioned STN-DBS trial (Schuepbach et al 2013). Interestingly, the PDQ39 improvement reported here exceeds those reported following other one-dimensional approaches (Schuepbach et al 2013;Tomlinson et al 2014;Gray et al 2022;Tödt et al 2022).…”
Section: Improvements Of Motor and Non-motor Symptoms As Well As Qolsupporting
confidence: 92%
“…First attempts to offer a multidisciplinary rehabilitation program for PD patients in a day-care unit in a district hospital obtained a ~ 4% improvement in health-related QoL after a 6-week treatment period (Trend et al 2002 ). Longer invasive neurostimulation studies report on improvements ranging between, e.g., 4.6 and 7.8 points (Schuepbach et al 2013 ; Tödt et al 2022 ). The ~ 9% improvement in the PDQ39 summary index reported in our cohort is in line with results reported in a previous short-term neurological day clinic (Fründt et al 2018 ) as well as the 24-month results of the aforementioned STN–DBS trial (Schuepbach et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, our research is not longitudinal and we are not able to trace long-lasting changes in IADL due to STN-DBS. Third, we do not report data on individual stimulation volumes and functional zones of the STN and their contribution to IADL changes (Tödt et al, 2022). Fourth, a modest sample size regarding DBS research and the apparent lack of cognitive decline after STN-DBS surgery in our sample might have prevented us from observing any significant interaction between the time of assessment and cognitive performance.…”
Section: Discussionmentioning
confidence: 93%
“…Deep brain stimulation (DBS) of the subthalamic nucleus (STN-DBS) is a standard treatment for medication-refractory movement symptoms of PD (Perlmutter and Mink, 2006;Bronstein et al, 2011;Okun, 2014;Mueller et al, 2020). A number of works have shown that this therapy is highly effective in regaining control over PD motor symptoms and improving patients' quality of life (QoL), as well as in reducing the levodopa equivalent daily dose (LEDD) (Tomlinson et al, 2010;Bratsos et al, 2018;Tödt et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation